Los carteles del periódico Tierra: construcción de la identidad del obrero colombiano (2014)
This work a review of the newspaper tries to do Tierra, Central Organ of the Communist party, in the period understood between the year 1932 to 1939, device of statement that was articulated to the activities of a political project that started arising in the decade of 1930. The review incorporates an analytical look of some of the images of the above mentioned newspaper, realized in xylography and applied to political cartels.